Male genital system of Ameiva ameiva (Squamata: Teiidae) - Maciel, Érica da Silva [UNESP]; Zieri, Rodrigo; de Almeida-Santos, Selma Maria [UNESP] (Wiley, 2024)
Understanding squamate reproductive morphology is crucial for investigating ecological, behavioral, and evolutionary questions. Here, we describe the anatomy and histology of the male genital system of Ameiva ameiva from southeastern Brazil. Ten adult males were dissected to characterize genital macroscopy and collect fragments of the testes, gonadoducts, and kidneys for histological examination. We examined 10 transverse histological sections per individual and measured the epithelial height of the epididymis and ductus deferens. The male reproductive system consists of a pair of yellowish oval testes, the rete testis, ductuli efferentes, epididymis, ductus deferens, ampulla ductus deferentis, sexual segment of the kidney (SSK), cloaca, and hemipenis. The hemipenis is elongated, cylindrical, and unilobed, with a sulcate face and an asulcate face, which has continuous fringes throughout its length. Seminiferous tubules exhibited germ cells at various stages. The epididymis is wider and more coiled than the ductus deferens. The rete testis has a simple squamous epithelium with long stereocilia, while the narrower ductuli efferentes are lined by a simple ciliated cuboidal epithelium. The epididymal epithelium is pseudostratified columnar, with basal and ciliated principal cells, whereas the ductus deferens epithelium is pseudostratified to simple cuboidal. The epididymal epithelium is 1.5 times taller than the ductus deferens epithelium. Here, we observed the SSK present in the cortex of the ventral region of the kidneys due to the hypertrophy of the distal convoluted tubules, as well as its secretory activity. Our findings will contribute to future research into the evolution of squamate reproductive morphology.
Keywords: ductus deferens; epididymis; hemipenis; reproductive morphology; rete testis; sexual segment of the kidney; testis